Performance improvement of an ultra-thin amorphous silicon solar cell using multilayers chirped diffraction back gratings. (1st March 2022) - Shahamat, Mehran Abdolrahimi; Heidarzadeh, Hamid; Bahador, Hamid
Abstract: In this paper, a systematic design of a novel back reflector using chirped grating structures is investigated for thin-film amorphous silicon (a-Si) solar cells. At first, a cell with an optimum ITO antireflecting layer is simulated and a photocurrent of 17.67 mA cm −2 is obtained. Then a conventional grating from SiO2 is evaluated and the maximum photocurrent of 18.97 mA cm −2 is calculated. Then a thin-film solar cell based on the chirped back grating is designed and the photocurrent is increased to 19.30 mA cm −2 . Also, their integrated optical absorption is compared for better understanding. To give a numerical comparison of the cells with a different number of chirped grating layers, a short circuit current for different numbers of grating layers is analyzed. It is shown that maximum current density is obtained for 5 layers grating with the chirped coefficient length of near 20 nm. It is believed that chirped back grating can be used to design higher performance thin film a-Si solar cells and the results are helpful for photovoltaic applications.